1999
DOI: 10.1016/s0022-2275(20)33519-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly simplified method for gas-liquid chromatographic quantitation of bile acids and sterols in human stool

Abstract: A simple method for the gas-liquid chromatographic quantitation of human fecal bile acids and sterols is described where bile acids are subjected to n-butyl ester derivatization, without prior isolation from the stool, followed by trimethylsilylation of the sterols and bile acids. Under these conditions, bile acid derivatives are well resolved from each other and from the trimethylsilyl ether derivatives of fecal sterols and no overlap occurs. The method was shown to be highly reproducible and recoveries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…We found that metabolites associated with primary and secondary bile acid metabolism subpathways were positively associated with CAC in AAs. Excess cholesterol is converted into bile acids in the liver and excreted from the body [ 30 ]. Compared to individuals without coronary artery disease (CAD), patients with CAD reportedly have lower fecal bile acid excretion, and this supports a potential protective effect of bile acid excretion on the development of CAD [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that metabolites associated with primary and secondary bile acid metabolism subpathways were positively associated with CAC in AAs. Excess cholesterol is converted into bile acids in the liver and excreted from the body [ 30 ]. Compared to individuals without coronary artery disease (CAD), patients with CAD reportedly have lower fecal bile acid excretion, and this supports a potential protective effect of bile acid excretion on the development of CAD [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cholesterol is mainly eliminated from the body via the liver in the form of bile acids [Batta et al 1999]. It is reasonable to speculate that a reduced ability to convert cholesterol to bile acids would lead to body cholesterol overload, with the subsequent development of atherosclerosis [Assmann et al 2006;Sudhop et al 2002;Rajaratnam et al 2000Rajaratnam et al , 1999Glucc et al1991].…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids are biological detergents and metabolic regulators required for proper lipid digestion and absorption. In addition, bile acids facilitate the excretion of cholesterol and other molecules, such as xenobiotics ( Batta et al, 1999 ). Multiple studies have reported a negative correlation between CHD and bile acid excretion, which is also confirmed in our study ( Assmann et al, 2006 ; Gylling et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%